2022
DOI: 10.1111/mmi.14884
|View full text |Cite
|
Sign up to set email alerts
|

SxsA, a novel surface protein mediating cell aggregation and adhesive biofilm formation of Staphylococcus xylosus

Abstract: Biofilm formation of staphylococci has been an emerging field of research for many years. However, the underlying molecular mechanisms are still not fully understood and vary widely between species and strains. The aim of this study was to identify new effectors impacting biofilm formation of two Staphylococcus xylosus strains. We identified a novel surface protein conferring cell aggregation, adherence to abiotic surfaces, and biofilm formation. The S. xylosus surface protein A (SxsA) is a large protein occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…In this process, the accumulation of polysaccharide intercellular adhesin (Pia) and adhesive proteins, such as accumulation-associated protein (Aap) and biofilm-associated protein (Bap), will aid protection against the host immune system facilitating virulence. This mechanism also promotes protection from antibiotic attack, further enhanced the development of resistance to antibiotics, which contributes to the survival of these strains and the severity of infection [ 14 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the accumulation of polysaccharide intercellular adhesin (Pia) and adhesive proteins, such as accumulation-associated protein (Aap) and biofilm-associated protein (Bap), will aid protection against the host immune system facilitating virulence. This mechanism also promotes protection from antibiotic attack, further enhanced the development of resistance to antibiotics, which contributes to the survival of these strains and the severity of infection [ 14 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, S. xylosus can be recovered at high frequencies two weeks after topical application onto the ears of C57BL/6 mice, which is in contrast to other staphylococcal species, such as S. aureus [287], suggesting that S. xylosus may express determinants that better allow it to survive on or adhere to murine skin. Two genome-encoded biofilm genes, bap and sxsA (a novel virulence factor), were recently identified in S. xylosus isolates from raw fermented sausages [182,288]. It was shown that only SxsA had a major importance in the biofilm formation of S. xylosus in vitro.…”
Section: Staphylococcal Infections In Micementioning
confidence: 99%
“…Numerous studies have demonstrated the correlation between the expression of these genes and the virulence of XDR strains (16). The biofilm-associated protein (Bap), encoded by the bap gene, is a high molecular weight surface protein that contains tandem repeats of domains involved in intercellular adhesion on bacterial cell surfaces (17). It is also associated with biofilm thickness and antibiotic resistance (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%